The Irrational Economist : Making Decisions in a Dangerous World. - Michel-Kerja, Erwann (Perseus Books Group, 2010)
Of the twenty most costly catastrophes since 1970, more than half have occurred since 2001. Is this an omen of what the 21st century will be? How might we behave in this new, uncertain and more dangerous environment? Will our actions be rational or irrational? A select group of scholars, innovators, and Nobel Laureates was asked to address challenges to rational decision making both in our day-to-day life and in the face of catastrophic threats such as climate changes, natural disasters, technological hazards, and human malevolence. At the crossroads of decision sciences, behavioral and neuro-